Peternakan dan Pertanian untuk Ketersedian Pakan Lokal Berkelanjutan di Desa Mekarharja, Kecamatan Purwaharja, Kota Banjar - Siti Nur Karimah; Afton Atabany (Lembaga Penelitian dan Pengabdian kepada Masyarakat, Institut Pertanian Bogor, 2019)
Station Lapang Agro Kreatif (SLAK) program aims to conduct feed logistics as an integration among farmers in Mekarharja Village. Application of feed logistics in the manufacture of fermented feed (silage), refinement of biological organic fertilizers (compost), and seeding of indigofera plants. Cattle farmers take advantage of local forage feed in meeting livestock consumption needs. Breeders understand more about providing feed for the dry season with a program for making fermented feed (silage), making biological organic fertilizer (compost) and indigofera plant cultivation. Breeders are easier to implement because the ingredients of the mixture are fewer and preferred by livestock from color and aroma.